Epistemic modals in early Modern English history texts. Analysis of gender variation - Francisco J. Álvarez Gil (Revista de Lingüística y Lenguas Aplicadas, 2018)
In the present study, samples of late Modern English scientific texts have been analysed to evaluate cases of epistemic modality as realised by modal verbs. The aim of this research was to detect if there exist variances in the way modals are used in historical texts from a gender perspective. For this, I have interrogated the Corpus History English Texts (1700-1900) which is part of The Coruña Corpus of English Scientific Texts, which contains history texts written by male and female authors. I have used the Coruña Corpus Tool for retrieval, although manual analyses have been carried out as well. Each of the occurrences found have been categorised according to their contextual meanings. The results obtained account for a high frequency on the usage of these modal verbs according to gender and the diverse pragmatic functions these modal verbs accomplish in the communicative process, such as mitigation and negative politeness. From a pragmatic perspective, epistemic modals have the potential to allow negotiation of meaning between writers and their audience among other functions.